(untitled) (Progressive Agriculture, 2016)
The purposes of the study were to determine the extent of awareness of the fishermen in managing fish sanctuary and to find out the relationships between the extent of awareness of the fishermen and their selected characteristics. Data were collected from 90 purposively selected fishermen (out of 105) from Ghosherpara Union of Melandah Upazila Under Jamalpur District. A pre-tested and structured interview schedule was used to collect data from the fishermen during the period of 19 March to 30 March, 2013. The findings indicated that majority of the respondents (74.5 percent) had medium awareness and 25.5 percent having high awareness. Out of ten selected characteristics, the fishermens age, level of education, fish culture experience, communication exposure and agricultural knowledge on fish sanctuary showed significant positive relationships with their extent of awareness in managing fish sanctuary. On the other hand, household size, farm size, annual family income, training exposure and credit received had no significant relationships with their extent of awareness in managing fish sanctuary. So, to increase awareness of the fishermen in managing sanctuary, proper guidance and strengthening fisheries extension service should be done by fisheries extension workers/ upazila fisheries officer through arranging different activities including training, field visit or using different communication media etc. Progressive Agriculture 27 (3): 339-345, 2016